Deep‐Red‐Emitting Colloidal Quantum Well Light‐Emitting Diodes Enabled through a Complex Design of Core/Crown/Double Shell Heterostructure. Issue 8 (10th December 2021) - Shabani, Farzan; Dehghanpour Baruj, Hamed; Yurdakul, Iklim; Delikanli, Savas; Gheshlaghi, Negar; Isik, Furkan; Liu, Baiquan; Altintas, Yemliha; Canımkurbey, Betül; Demir, Hilmi Volkan
Abstract: Extending the emission peak wavelength of quasi‐2D colloidal quantum wells has been an important quest to fully exploit the potential of these materials, which has not been possible due to the complications arising from the partial dissolution and recrystallization during growth to date. Here, the synthetic pathway of (CdSe/CdS)@(1‐4 CdS/CdZnS) (core/crown)@(colloidal atomic layer deposition shell/hot injection shell) hetero‐nanoplatelets (NPLs) using multiple techniques, which together enable highly efficient emission beyond 700 nm in the deep‐red region, is proposed and demonstrated. Given the challenges of using conventional hot injection procedure, a method that allows to obtain sufficiently thick and passivated NPLs as the seeds is developed. Consequently, through the final hot injection shell coating, thick NPLs with superior optical properties including a high photoluminescence quantum yield of 88% are achieved. These NPLs emitting at 701 nm exhibit a full‐width‐at‐half‐maximum of 26 nm, enabled by the successfully maintained quasi‐2D shape and minimum defects of the resulting heterostructure. The deep‐red light‐emitting diode (LED) device fabricated with these NPLs has shown to yield a high external quantum efficiency of 6.8% at 701 nm, which is on par with other types of LEDs in this spectral range. Abstract : A synthetic protocol is developed to increase the thickness of CdSe‐based nanoplatelets (NPLs). These NPLs emit at 701 nm with a quantum yield of 88%, and their deep‐red light‐emitting diode (LED) device is shown to yield a high external quantum efficiency of 6.8% at 701 nm, on par with other types of LEDs in this spectral range.